Fredholmness of Combinations of Two Idempotents (European Journal of Pure and Applied Mathematics, 2010)
If P and Q are two idempotents on a Hilbert space, in this paper, we prove that Fredholmness of aP+bQ-cPQ is independent ofthe choice of a, b, c with $ab eq 0$.